Total 'Quality Management (TQM) and University of Jaffna Library: an approach to the acquisition process - Ketheeswaren, S.; Arulanantham, S. (University Librarians Association, 2010)
Most of the organizations are becoming product and service oriented and it is obvious that their target is to provide products and services to their users on commercial basis. Total Quality Management (TQM), provides the tools and the direction to improve quality of products and services. In this context, University Libraries has always been committed to provide a high quality of services to its users. It is believed that this can be achieved by implementing TQM tools and measures in the University Libraries. The paper points out the evolution, and stages of implementation of TQM in University Libraries. It discusses the experiences of Jaffna University library service while applying TQM to its acquisition process.
Keywords: Library Quality Management; Acquisition Process; TQM